The Moderating Role of Information Media in Generation Z’s Sharia Investment Decisions - Khavid Normasyhuri; Adli Rikanda Saputra; Harold Kevin Alfredo; Ahsanal Huda; Rubi Febriansyah (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2025)
This study examines the relationships among information quality, subjective norms, and behavioral control in influencing Generation Z’s Islamic investment decisions during the COVID-19 pandemic, while assessing the moderating role of information media. A quantitative method was employed using SmartPLS 3.0 for statistical analysis. Primary data were collected through purposive sampling of 500 Islamic investors between December 2021 and December 2022 using Google Forms, and all variables were measured with a Likert scale. The findings show that information quality and behavioral control had a positive and significant impact on Generation Z’s Islamic investment decisions during the pandemic. In contrast, subjective norms exhibited a negative relationship, implying that social pressure and external expectations did not consistently promote sharia-based investment behavior. Information media acted as a moderating factor that strengthened the relationship among information quality, subjective norms, and behavioral control in investment decision-making. The results suggest that digital media platforms provided access to timely, accurate, and relevant information, enhancing confidence among young Muslim investors. However, Islamic investment instruments remain limited compared to conventional alternatives. Therefore, expanding and diversifying Islamic financial products is essential to assist investors in developing sustainable and Sharia-compliant investment portfolios that promote ethical growth and long-term economic resilience.